UPTAKE OF Co(II), Pb(II) AND Ni(II) IONS BY Annona senegalensis STEM BARK BIOCHAR FROM AQUEOUS SOLUTION: OPTIMIZATION, KINETIC AND THERMODYNAMIC STUDIES - Omale, Aminu; Ekere, Nwachukwu R.; Omale, Jamila A.; Ihedioha, Janefrances N.; Egu, Samuel A. (FUDMA JOURNAL OF SCIENCES, 2024)
The concern for heavy metal pollution in the environment is especially so since they are non-biodegradable. The use of agro materials in the removal of these heavy metal pollutants has been recognized as a low-cost alternative to the costly conventional remediation techniques. The equilibrium sorption of the chemically activated Anonna senegalensis stem bark was investigated. Using standard techniques, the physicochemical properties of activated carbon (MAASC) were ascertained. By using a simultaneous batch adsorption approach, the adsorption of Co2+, Pb2+, and Ni2+ onto MAASC was examined as a function of pH, solution temperature, initial metal ion concentration, agitation time, adsorbent dose, particle size, and carbonization temperature. The equilibrium sorption data generated were fitted into Langmuir, Freundlich, Temkin and Dubinin-Radushkevich isotherm models as well as pseudo first-order, pseudo-second-order and intraparticle diffusion kinetic models. From the obtained results, it was discovered that the Langmuir isotherm provided the best match conformation of all the models, except for Pb2+, which was best for Freundlich with an R2 of 0.95. Physisorption was shown to be the mechanism by Dubinin-Radushkevich. For Co2+, Pb2+, and Ni2+, respectively, the pseudo second-order kinetic model had R2 values of 0.997, 0.999, and 0.999 that best matched the data. Both intraparticle diffusion and the boundary layer effect also contributed to regulating the rates of the adsorption process. The study’s thermodynamic results showed that Ho for Co2+, Pb2+, and Ni2+ were 27.51, 19.70, and 13.37 KJ/mol, respectively. These values are all positive and suggest an endothermic reaction, supporting the physisorption mechanism.